2020
DOI: 10.31234/osf.io/dbg62
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Indirect Effects of Disordered Social Media Use on Stress and Depression via Fear of COVID-19

Abstract: The 2019 novel coronavirus disease (COVID-19) is a global threat that has negative impacts on individuals’ physical and mental health. Here, we explore if disordered social media use promotes fear of COVID-19, which in turn increases stress and depression in users. The study also explores several risk and protective factors that may affect the relationship between fear of COVID-19 and stress and depression. There were 174 participants that completed an online survey that measured disordered social media use, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…SMU was positively correlated with avoidant coping at both T1 and T6, suggesting that adolescents may use social media as an avenue to avoid unpleasant thoughts or feeling related to stress of the pandemic. This is consistent with prior work showing that adolescents use social media to disengage from unpleasant thoughts and emotions (McNicol & Thorsteinsson, 2017; Stockdale & Coyne, 2020; Tillman, 2020). SMU by itself also moderated anxiety change, although follow‐up tests revealed only a marginal effect of reduced SMU predicting decreasing anxiety.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…SMU was positively correlated with avoidant coping at both T1 and T6, suggesting that adolescents may use social media as an avenue to avoid unpleasant thoughts or feeling related to stress of the pandemic. This is consistent with prior work showing that adolescents use social media to disengage from unpleasant thoughts and emotions (McNicol & Thorsteinsson, 2017; Stockdale & Coyne, 2020; Tillman, 2020). SMU by itself also moderated anxiety change, although follow‐up tests revealed only a marginal effect of reduced SMU predicting decreasing anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Further, adolescents may use SM as an avenue to deploy avoidant coping by self‐distracting from negative emotions (McNicol & Thorsteinsson, 2017; Stockdale & Coyne, 2020). Tillman (2020) found that putatively maladaptive SMU, conceptualized as compulsive behaviors comparable to behavioral addictions (Van den Eijnden et al, 2016) (e.g., SMU as escapism), predicted elevated stress. Indeed, avoidant coping has been implicated as a potential mechanism underlying the association between elevated psychological distress and internet addiction (Cheng et al, 2015; McNicol & Thorsteinsson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The current study confirms that COVID-19 related stress can be significantly predicted by excessive usage of social media. In terms of risk and protective factors, it was discovered that the link between COVID-19 fear and stress is stronger in older persons than it is in younger people (Tillman et al, 2019). Adolescents can utilize social media as a positive coping tool to deal with nervous feelings during the COVID-19 quarantine (Cauberghe et al, 2021); and stress is predicted indirectly by disordered social media use due to a fear of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…From a psychological perspective, being active online has a both negative and positive impact on well-being, mental health and interpersonal relationships. Tillman et al (2020) found that virtual communication and frequent online communication with friends were positively associated with severe depressive tendencies during the pandemic. In contrast, Bessiere et al (2010) report a significant correlation between the use of the Internet for communication purposes, especially when it concerns family and friends, and a reduction in the severity of symptoms of depression.…”
Section: Page 226mentioning
confidence: 95%